Prevalência de sobrepeso e obesidade em escolares do município de Fernandópolis – São Paulo - Silva, Carolina Penteado Guerra (2010)
The prevalence of overweight and obese children and adolescents has increased in recent years both in developed and in developing countries. This fact is attributed to two main mechanisms: a decrease in energy expenditure due to sedentary lifestyle and increased caloric intake. The aim of this study was to evaluate the prevalence of overweight and obesity in schoolchildren of both sexes, aged 6 -10 years, enrolled in the private and public schools in the city of Fernandópolis - SP, associating the determining factors, as the socio-economic, physical activity, dietary habits and duration of breastfeeding. We evaluated 319 students who were 170 females (53%) and 149 males (47%); for the classification of nutritional status were used BMI percentile charts for children aged 5 to 19 years, suggested by WHO. It was found that 160 students (50%) were eutrophic, 71 students (22%) were overweight, 67 students (21%) were obese and 21 (7%) with BMI under the ideal percentage for their age. These data are consistent with findings in research conducted in Brazil and worldwide. Factors such as school formation of the person responsible for these children and the number of people living at home are positively associated with the prevalence of overweight and obesity, it was observed that 45% out of the 138 schoolchildren who are overweight, had their keepers with complete high school and 39% with college or post-graduation. Among students who are overweight, 70% live in households with up to four people and 30% live in households with five or more people. The preference on the occupation of free time shows a tendency for activities with reduced energy expenditure, such as playing video games, watching TV or using the computer to replace the activities with higher energy expenditure, such as sports and games. Regarding the duration of breastfeeding there is a tendency to early weaning, because 35% of children were breastfed until the sixth month of life and 23% had breast milk replaced by cow milk, supporting the importance of breastfeeding as a protective effect against excessive weight. Regarding food frequency, although the responsible for the students reported that 42% of cases always offer healthy food, there was a divergence from the results obtained in the frequency that the students and their responsible consume food, both showing a consumption of essential food and improper food in their routine. The results of this study reinforce the need and importance of implementing programs of food re-education, nutritional education and physical activity related to health promotion since the early grades of elementary school and extended to parents or guardians.